THE CORRELATION OF FAST FOOD CONSUMPTION AND PHYSICAL ACTIVITY WITH STUDENT MENTAL HEALTH DISORDERS DURING PANDEMIC - Riska Maya Sari; Abdul Salam; Veni Hadju; Citrakesumasari; Rahayu Indriasari; Devintha Virani (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Introduction: During the pandemic period, a social restriction policy has been implemented which has an impact on all aspects of life. One of them has an impact on students' mental health which can trigger anxiety or depression because they spend more time at home. It can also be influenced by several factors such as diet and physical activity. Objective: To determine the correlation between fast food consumption and physical activity with anxiety and depression. Methods: This study used a cross-sectional design. The research sample was students from the Hasanuddin University health sciences group, totaling 189 people, and was selected using simple random sampling. The instruments used in this study were SQ-FFQ to measure fast food consumption, GPAQ to measure physical activity, and DASS-42 to measure mental health. Results: The results showed that most of the respondents rarely consumed fast food (92.1%) and the majority had moderate levels of physical activity (46.6%). The results of the bivariate analysis showed p-value>0.005 for fast food consumption with anxiety, depression, and general mental disorders and physical activity with general mental disorders. Meanwhile, for physical activity with anxiety and depression obtained p-value <0.005. Conclusion: There is no correlation between the consumption of fast food with anxiety, depression, and general mental disorders. There is a correlation between physical activity with anxiety and depression, but there is no correlation between physical activity and general mental disorders. Students are expected to be able to implement a healthy lifestyle during the pandemic by eating a good diet and increasing physical activity. Keywords: Fast Food, Physical Activity, Anxiety, Depression